2022
DOI: 10.3389/fpsyg.2022.1009347
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone addiction and cross-cultural adjustment among overseas Chinese students: The role of emotion regulation beliefs and strategies

Abstract: BackgroundFew studies have focused on the cross-cultural adjustment of Chinese students studying in Belarus with the size of this group increasing in recent years. The current study aimed to map the process of cross-cultural adjustment onto various factors including childhood emotional neglect, emotion regulation beliefs, emotional regulation strategies, and smartphone addiction in the international students. Emotional regulation strategy and emotion regulation beliefs could perform as key parts in adapting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…This finding suggests that university students, regardless of the emotion regulation strategy used, regulate their emotions by seeking help from their mobile phones when encountering difficulties. A recent study found that those who tend to use cognitive reappraisal strategies have higher levels of smartphone addiction [ 59 ]. They suggested that this may depend on environmental changes and individual coping preferences, as well as the fact that cognitive reappraisal strategies rationalise mobile phone use and lead to addiction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that university students, regardless of the emotion regulation strategy used, regulate their emotions by seeking help from their mobile phones when encountering difficulties. A recent study found that those who tend to use cognitive reappraisal strategies have higher levels of smartphone addiction [ 59 ]. They suggested that this may depend on environmental changes and individual coping preferences, as well as the fact that cognitive reappraisal strategies rationalise mobile phone use and lead to addiction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that those who tend to use cognitive reappraisal strategies have higher levels of smartphone addiction [ 59 ]. They suggested that this may depend on environmental changes and individual coping preferences, as well as the fact that cognitive reappraisal strategies rationalise mobile phone use and lead to addiction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation